Early limb patterning in the direct‐developing salamander Plethodon cinereus revealed by sox9 and col2a1. Issue 3 (12th March 2018) - Kerney, Ryan R.; Hanken, James; Blackburn, David C.
Abstract : Direct‐developing amphibians form limbs during early embryonic stages, as opposed to the later, often postembryonic limb formation of metamorphosing species. Limb patterning is dramatically altered in direct‐developing frogs, but little attention has been given to direct‐developing salamanders. We use expression patterns of two genes, sox9 and col2a1, to assess skeletal patterning during embryonic limb development in the direct‐developing salamander Plethodon cinereus . Limb patterning in P. cinereus partially resembles that described in other urodele species, with early formation of digit II and a generally anterior‐to‐posterior formation of preaxial digits. Unlike other salamanders described to date, differentiation of preaxial zeugopodial cartilages (radius/tibia) is not accelerated in relation to the postaxial cartilages, and there is no early differentiation of autopodial elements in relation to more proximal cartilages. Instead, digit II forms in continuity with the ulnar/fibular arch. This amniote‐like connectivity to the first digit that forms may be a consequence of the embryonic formation of limbs in this direct‐developing species. Additionally, and contrary to recent models of amphibian digit identity, there is no evidence of vestigial digits. This is the first account of gene expression in a plethodontid salamander and only the second published account of embryonic limb patterning in a direct‐developing salamander species.